Development of Sustainable Agrotourism at Sein Farm (Sekemala Integrated Farm) Bandung City - Muhammad Fakhri Ramadhan; Muhammad Najih Fasya (Architectural Research Journal, 2023)
Tourism development in Ujungberung District, Bandung City is directed towards the theme of agrotourism, which is realized in the Sein Farm (Sekemala Integrated Farm). Sein Farm is a program from the Bandung City Food and Agriculture Security Service (DKPP) in the form of integrating agriculture on urban land which is a superior program as well as a means of agricultural educational tourism. Activities at Sein Farm include seeding, breeding and processing waste from activities, which is reprocessed into fertilizer for the nursery. Plant and livestock seeds resulting from activities at Sein Farm will then be distributed free of charge to the community around Sein Farm and Bandung City. We then analyzed the concept of integrated and sustainable agriculture in the form of tourist attraction analysis, social, economic and environmental analysis and SWOT analysis, the results of which were future strategic planning at the Sein Farm location.